Intensity, recovery kinetics and well-being indices are not altered during an official FIFA futsal tournament in Oceanian players. Issue 4 (16th February 2016) - Charlot, Keyne; Zongo, Paul; Leicht, Anthony Scott; Hue, Olivier; Galy, Olivier
Abstract: Physiological responses (intensity and recovery kinetics) and well-being indices were examined during a 4-day FIFA international tournament. Ten outfield New Caledonian players (age: 25.5 ± 3.8 years; height: 170 ± 7 cm; weight: 70.7 ± 8.6 kg) were assessed during the four matches. Players' aerobic and anaerobic capacities were measured before the tournament while heart rate (HR), intra-matches recovery and well-being indices (Hooper index) were measured throughout the tournament. HR (168 ± 8 bpm), exercise intensity (83.4 ± 2.3% of HR reserve) and recovery indices were similar throughout the tournament. Well-being indices were largely alike during the tournament while rating of perceived exertion increased throughout the tournament that was not associated with HR or well-being indices. High aerobic and anaerobic capacities were associated with high match intensities and slow recovery indices. In summary, match intensity assessed by HR, recovery kinetics and well-being of Oceanian futsal players were not modified during a 4-day FIFA futsal tournament. Assessment of aerobic and anaerobic capacities may be useful to select players for optimal performance during this type of international tournament.